PENGARUH EDUKASI GIZI MELALUI PERMAINAN ULAR TANGGA DAN BOOKLET TERHADAP PENGETAHUAN, SIKAP, DAN PRAKTIK PENCEGAHAN ANEMIA PADA REMAJA PUTRI - Hisanah, Raniah; Nuryanto, Nuryanto; Rahadiyanti, Ayu; Wijayanti, Hartanti Sandi (Journal of Nutrition College, 2023)
ABSTRACTBackground: Adolescent girls anemia in Indonesia is still quite high. One of the effective alternatives for preventing anemia is nutrition education through snakes and ladders games and booklets, which are able to attract attention and stimulate curiosity.Objective: The aim of this research is to analyze the effect of nutrition education through snakes and ladders games and booklets on increasing knowledge, attitudes, and practices for preventing anemia in adolescent girls.Methods: A quasi-experimental study with a pre-post group design was conducted on 34 adolescent girls subjects at SMP Ma'had Islam Semarang, which were selected by total sampling. Then it was divided into two groups by quota sampling. The first group was given nutrition education through snakes and ladders games, the second group through booklets. Knowledge, attitude, and practice data were obtained through a structured questionnaire, and evidence of practice data was obtained through interviewing for food intake with the FFQ method. Effect analysis using a paired t-test and an independent t-test.Results: There were differences in the average knowledge (p<0.001), attitudes (p<0.001), and practice (p<0.001) of anemia prevention before and after nutrition education through snakes and ladders games and booklets. However, knowledge (p = 0.179), attitude (p = 0.231), and practice (p = 0.179) of anemia prevention between the two groups have no difference. Conclusion: There is an effect of nutrition education through snakes and ladders games and booklets is equally effective in increasing knowledge, attitudes, and practices of anemia prevention in adolescent girls.Keywords: nutrition education snakes and ladders games, knowledge, attitudes, practices, anemia ABSTRAKLatar Belakang: Anemia remaja putri di Indonesia masih cukup tinggi. Salah satu alternatif efektif dalam pencegahan anemia, yaitu edukasi gizi melalui permainan ular tangga dan booklet yang mampu menarik perhatian dan menstimulus rasa keingintahuan.Tujuan: Tujuan penelitian ini adalah untuk menganalisis pengaruh edukasi gizi melalui permainan ular tangga dan booklet terhadap peningkatan pengetahuan, sikap, dan praktik pencegahan anemia pada remaja putri.Metode: Penelitian quasy experimental dengan pre-post group design dilakukan pada 34 subjek remaja putri di SMP Ma’had Islam Semarang yang dipilih secara total sampling. Lalu dibagi menjadi dua kelompok dengan quota sampling. Kelompok pertama diberikan edukasi gizi melalui permainan ular tangga, kelompok kedua melalui booklet. Data pengetahuan, sikap, dan praktik diperoleh melalui kuesioner terstruktur, serta data bukti praktik diperoleh melalui wawancara asupan makan dengan FFQ. Analisis pengaruh menggunakan uji paired t-test dan independent t-test.Hasil: Terdapat perbedaan rerata pengetahuan (p<0,001), sikap (p<0,001), dan praktik (p<0,001) pencegahan anemia sebelum dan sesudah edukasi gizi melalui permainan ular tangga dan booklet. Namun pengetahuan (p=0,179), sikap (p=0,231), dan praktik (p=0,179) antara kedua kelompok tidak terdapat perbedaan. Simpulan: Edukasi gizi melalui permainan ular tangga dan booklet sama efektifnya dalam meningkatkan pengetahuan, sikap, dan praktik pencegahan anemia pada remaja putri.  Kata Kunci: edukasi gizi ular tangga, pengetahuan, sikap, praktik, anemia